2020
DOI: 10.1080/09540105.2020.1789071
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect and mechanism of fucoidan on intestinal mucosal barrier function in NOD mice

Abstract: This study was to evaluate the protective effect of fucoidan on the intestinal mucosal barrier in non-obese diabetic mice (NOD). Twenty NOD mice were randomly assigned to two groups: the control group and the fucoidan intervention group which were fed with fucoidan at a concentration of 600 mg/kg BW (body weight) per day for five weeks. Mice treated with fucoidan had a significant improvement in glycemic control, and the proportions of Th1/Th2/Th17 cells and the levels of endotoxin, DAO and D-LA were reduced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…Meanwhile, damage to the intestinal barrier could allow diamine oxidase, d ‐lactic acid and endotoxin to penetrate the internal circulation, a sign of intestinal permeability. This finding was further supported by a study in non‐obese diabetic mice, a model of autoimmune diabetes; after fucoidan intervention (600 mg kg −1 ), the expression of occludin, zonula occludens 1, claudin‐1 was increased, and the levels of diamine oxidase, d ‐lactic acid and endotoxin were reduced 10 …”
Section: Diabetesmentioning
confidence: 57%
See 2 more Smart Citations
“…Meanwhile, damage to the intestinal barrier could allow diamine oxidase, d ‐lactic acid and endotoxin to penetrate the internal circulation, a sign of intestinal permeability. This finding was further supported by a study in non‐obese diabetic mice, a model of autoimmune diabetes; after fucoidan intervention (600 mg kg −1 ), the expression of occludin, zonula occludens 1, claudin‐1 was increased, and the levels of diamine oxidase, d ‐lactic acid and endotoxin were reduced 10 …”
Section: Diabetesmentioning
confidence: 57%
“…Our previous research found that fucoidan‐treatment (600 mg kg −1 ) notably reduced the levels of IFN‐γ, IL‐17A and down‐regulated the IFN‐γ/IL‐4 ratio in mice. In other words, fucoidan regulated the equilibrium of Th1/Th2/Th17 10 …”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, TEM can reveal the severe damage of the structure of mouse intestinal villi. 25,26 DSS can induce the activation of TLR4 signal in the mouse intestine. CNQX can significantly alleviate this damage and attenuate he inflammatory response in the mouse intestine.…”
Section: Discussionmentioning
confidence: 98%
“…DSS can destroy the intestinal mucosa of mice and obviously damage the mucosal barrier of mice, which is manifested as the down‐regulated expression of tight junction protein (occludin and claudin‐1). Meanwhile, TEM can reveal the severe damage of the structure of mouse intestinal villi 25,26 . DSS can induce the activation of TLR4 signal in the mouse intestine.…”
Section: Discussionmentioning
confidence: 99%